Morphological Types of Epithelial Origin Ovarian Tumours - Hadia Nazar, Kheem Chand Lohano, Ashok Kumar, Aruna Kumari Hira, Azra Idris, Lata Bai Lohano, Aayat Ellahi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the various morphological types of epithelial origin ovarian tumors. Methods: The study involved cases that were presented to the Pathology department between January 2015 to December 2020. Epithelial ovarian tumors that were diagnosed as either benign, borderline, or malignant were analyzed. The inclusion criteria involved pathological specimens of ovarian tumors consisting of cells that are epithelial in origin. Clinical records, ultrasounds, and histopathological investigations of the patients were accessed from the hospital database for analysis. Results: A total of 309 cases were reviewed. Out of these, ovarian epithelial tumors made up at least four-fifths of the total tumors i.e. 258(83.5%). Non-epithelial origin of ovarian tumors only consisted of 51(16.5%) cases. Out of these 153(49.84%) cases were diagnosed as serous, 88(28.48%) as mucinous. A total of 175(61.4%) tumors were benign, 15(5.81%) were borderline, and 68 (26.3%) were malignant. The patients with malignant serous tumors (43.24±13.99 years) were considerably older than individuals with benign (34.54 ± 13.16 years) and borderline (32.71±13.79 years) serous tumors. Conclusion: The present study concludes that epithelial ovarian cancer is the most commonly encountered lesion in our population. Benign and borderline tumors involve slightly younger age groups, mostly below forty years of age. Keywords: Carcinoma, Epithelial-origin tumors, malignancy, ovarian tumors